The incidence of tuberculosis among adolescents and young adults: a global estimate. Issue 2 (22nd February 2018) - Snow, Kathryn J.; Sismanidis, Charalambos; Denholm, Justin; Sawyer, Susan M.; Graham, Stephen M.
Historical data show that the risk of tuberculosis increases dramatically during adolescence, and young people face unique challenges in terms of case detection and effective treatment. However, little is known about the burden of tuberculosis among young people in the modern era. This study aimed to provide the first estimates of the global and regional incidence of tuberculosis among young people aged 10–24 years. Using the World Health Organization (WHO) database of tuberculosis notifications for 2012, we estimated the burden of tuberculosis among young people by WHO region. Adjustments were made for incomplete age disaggregation and underreporting, using supplementary data from several countries representing diverse tuberculosis epidemics. We estimate that 1.78 million (uncertainty interval (UI) 1.23–3.00 million) young people developed tuberculosis in 2012, accounting for 17% of all new tuberculosis cases globally. Young people in the WHO South East Asian Region (721 000, UI 473 000–1.35 million) and the WHO African Region (534 000, UI 359 000–912 000) experienced the greatest number of tuberculosis episodes. Young people suffer a considerable burden of tuberculosis. Age-specific burden of disease estimation for this age group is complicated by incomplete age disaggregation of tuberculosis data, highlighting the importance of continued surveillance system strengthening. An estimated 1.78 million young people (aged 10–24 years) around the world developed tuberculosis in 2012 http://ow.ly/o9vq30hoepv